Lean product development a manager's guide - Mynott, Colin (The Institution of Engineering and Technology, 2012)
This book is about how you manage the business process of developing products from strategy through design, to testing and service feedback. You can apply it to manufactured and service products, whether completely new or just a minor change. It's not an instruction manual on tools and techniques. These are explained in Chapter 11; Chapter 12 gives references on their detail.